Large-scale identification of odorant-binding proteins and chemosensory proteins from expressed sequence tags in insects - Xu, Ya-Long; He, Peng; Zhang, Lan; Fang, Shao-Qing; Dong, Shuang-Lin; Zhang, Yong-Jun; Li, Fei (BMC genomics, 2009)
Insect odorant binding proteins (OBPs) and chemosensory proteins (CSPs) play an important role in chemical communication of insects. Gene discovery of these proteins is a time-consuming task. In recent years, expressed sequence tags (ESTs) of many insect species have accumulated, thus providing a useful resource for gene discovery. We have developed a computational pipeline to identify OBP and CSP genes from insect ESTs. In total, 752,841 insect ESTs were examined from 54 species covering eight Orders of Insecta. From these ESTs, 142 OBPs and 177 CSPs were identified, of which 117 OBPs and 129 CSPs are new. The complete open reading frames (ORFs) of 88 OBPs and 123 CSPs were obtained by electronic elongation. We randomly chose 26 OBPs from eight species of insects, and 21 CSPs from four species for RT-PCR validation. Twenty two OBPs and 16 CSPs were confirmed by RT-PCR, proving the efficiency and reliability of the algorithm. Together with all family members obtained from the NCBI (OBPs) or the UniProtKB (CSPs), 850 OBPs and 237 CSPs were analyzed for their structural characteristics and evolutionary relationship. A large number of new OBPs and CSPs were found, providing the basis for deeper understanding of these proteins. In addition, the conserved motif and evolutionary analysis provide some new insights into the evolution of insect OBPs and CSPs. Motif pattern fine-tune the functions of OBPs and CSPs, leading to the minor difference in binding sex pheromone or plant volatiles in different insect Orders.